2009
DOI: 10.1080/15419060902957296
|View full text |Cite
|
Sign up to set email alerts
|

Time Lapse Monitoring of CaCo-2 Cell Shapes and Shape Dependence of the Distribution of Integrin β1 and F-Actin on their Basal Membrane

Abstract: CaCo-2 cell line is a model system for cell differentiation. For the effective use of CaCo-2 cells, it is important to understand how their growth depends on environmental conditions. The authors grew them on laminin-1, fibronectin, and collagen-1 adsorbed to glass and polystyrene. The time lapse technique was applied to follow their growth and shape changes for 21.5 h post seeding. The results upgraded the auhtors' previous findings about the series of consecutive shape changes that occur post seeding. Most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Caco-2 cells were observed to adhere onto the ECM coated Teflon membrane within 30 min after cell seeding. During the phase of active growth, it was observed that once the flow of cell culture media was started (first 24 hrs of cell culture), the Caco-2 cells spread out [ 57 ], although, in some regions the cells grew in clusters ( Fig 4A ). It was also observed that flowing DMEM at 0.5μl/ml for the first 16-24hrs across the cells, was sufficient to wash-out the unattached Caco-2 cells ( S6B Fig ) without releasing the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Caco-2 cells were observed to adhere onto the ECM coated Teflon membrane within 30 min after cell seeding. During the phase of active growth, it was observed that once the flow of cell culture media was started (first 24 hrs of cell culture), the Caco-2 cells spread out [ 57 ], although, in some regions the cells grew in clusters ( Fig 4A ). It was also observed that flowing DMEM at 0.5μl/ml for the first 16-24hrs across the cells, was sufficient to wash-out the unattached Caco-2 cells ( S6B Fig ) without releasing the cells.…”
Section: Resultsmentioning
confidence: 99%
“…B). Although other TLVM studies document live Caco2 cell phenomena , they often indicate merely that the cells were incubated on a heated stage or in a chamber at 37 degrees Celsius and do not demonstrate that the cells themselves experience a physiological environment and behave as expected under physiological conditions. Our device measures conditions in the immediate environment surrounding the cells and recapitulates the pH, humidity, and cell growth rate maintained by a standard incubator.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of ECM membranes in cell culture were demonstrated by Wang et al, who compared colonic cell culture on three different fibronectin-coated devices. A membrane-less device showed a decline in cell viability after Day 1 and maintained round cell morphology, which indicates a lack of differentiation 139 . The viability further decreased to 76% on Day 5, indicating an early apoptotic phase 136 .…”
Section: Biological Ecm Protein Membranesmentioning
confidence: 98%